Suspect screening of OH-PAHs and non-target screening of other organic compounds in wood smoke particles using HR-Orbitrap-MS. (November 2016) - Avagyan, Rozanna; Åberg, Magnus; Westerholm, Roger
Abstract: Wood combustion has been shown to contribute significantly to emissions of polycyclic aromatic hydrocarbons and hydroxylated polycyclic aromatic hydrocarbons, compounds with toxic and carcinogenic properties. However, only a small number of hydroxylated polycyclic aromatic hydrocarbons have been determined in particles from wood combustion, usually compounds with available reference standards. In this present study, suspect and non-target screening strategies were applied to characterize the wood smoke particles from four different wood types and two combustion conditions with respect to hydroxylated polycyclic aromatic hydrocarbons and other organic compounds. In the suspect screening, 32 peaks corresponding to 12 monohydroxylated masses were tentatively identified by elemental composition assignments and matching of isotopic pattern and fragments. More than one structure was suggested for most of the measured masses. Statistical analysis was performed on the non-target screening data in order to single out significant peaks having intensities that depend on the wood type and/or combustion condition. Significant peaks were found in both negative and positive ionization modes, with unique peaks for each wood type and combustion condition, as well as a combination of both factors. Furthermore, structural elucidation of some peaks was done by comparing the spectra in the samples with spectra found in the spectral databases. Six compounds were tentatively identified in positive ionization mode, and 19 in negative ionization mode. The results in this present study demonstrate that there are significant overall differences in the chemistry of wood smoke particles that depends on both the wood type and the combustion condition used. Highlights: Suspect and non-target screening were used to characterize wood smoke particles. Suspect screening was done in order to identify OH-PAH isomers. 32 peaks corresponding to 12 OH-PAH masses were tentatively identified. Non-target screening involved statistical analysis and tentative identification of unknowns. Unique compounds for each wood type and burning condition were identified.